On the issue of cooperation of States in the field of organ donation and transplantation - N. A. Boenko; M. G. Minina (Вестник трансплантологии и искусственных органов)
In today’s world, state cooperation is carried out in almost all aspects of political, social and economic life. The interaction of States on high technologies in medicine is not something new and is carried out in a wide range of clinical areas. The cooperation of States in the field of organ donation and transplantation is not limited to the exchange of clinical experience between specialists from different countries or the provision of medical care in a particular case. On the one hand, this direction affects many aspects of social life of man, and needs special legal regulation. On the other hand, it is an effective organizational mechanism, the use of which by States can contribute to saving the lives and health of their own citizens through the inter-state exchange of donor organs. The most important goal of inter-state cooperation is to unite the efforts of the relevant state institutions and services to combat the illegal organ donation and transplantation tourism.